Umm el-Qaab (Abydos), Ägypten. Untersuchungen zum Osiriskult in Abydos vom Alten Reich bis in die Spätzeit. Die Arbeiten der Jahre 2016 und 2017 - Effland, Ute; Effland, Andreas (e-Forschungsberichte des DAI, 2017)
The cult of the god Osiris in Abydos led to countless ritual and votive material in Umm el-Qaab, the former ancient necropolis of the early dynastic kings of Egypt. The focus of the campaign and further work carried out in 2016 and 2017 focused on conservatory measures on several in situ deposits. These included several wooden boxes and a fragile cult figure of the god. One focus of the investigations of small-scale finds was the documentation of seal imprints from the time of the Middle Kingdom up to the 30th dynasty.